Blood flow restriction training for an individual with Kellgren–Lawrence grade 4 ankle osteoarthritis following childhood clubfoot repair: A case report - Petersson, Naaja; Jørgensen, Stian Langgård (Physiotherapy theory and practice, 2025)
Ankle osteoarthritis (OA) is a disease involving pain and decreased physical function which can attenuate the tolerance to perform high-load resistance training. Low-load blood flow restriction (BFR) training has been demonstrated to improve muscle strength, muscle size, and physical function in patients suffering from OA. We examined the effects of 12 weeks of BFR-training performed 4 times a week in an individual with Kellgren-Lawrence (KL) grade 4 ankle OA. A 32-year-old woman with KL grade 4 right ankle OA subsequent to a clubfoot repair in childhood performed 12 weeks of BFR-training. Four exercises with concurrent blood flow restriction (60% of arterial occlusion pressure) targeting the lower leg were performed 4 times/week. The following outcome measures were collected at baseline and 12 weeks after BFR-training: The Foot and Ankle Outcome Score (FAOS), calf circumference, maximal isometric muscle strength, single-leg heel raise test, single-leg stance test, and lateral side-hop test. Adherence to the training was 93.75%. The patient demonstrated improvements in FAOS subscale symptoms, pain, and sports/recreational activities by 19-47 points (minimal detectable change (MDC) = 18-21.5 points); maximal muscle strength in plantarflexion (36%), eversion (55%), and inversion (38%) (MDC for plantarflexion = 16.81-29.97%). The single-leg heel raise test and the lateral side-hop test improved with 66% and 51%, respectively. Calf circumference was maintained. BFR-training improved patient-reported outcomes, lower leg muscle strength, and physical function in an individual suffering from KL grade 4 ankle OA following childhood clubfoot repair.